2009
DOI: 10.1016/j.nuclphysbps.2009.03.083
|View full text |Cite
|
Sign up to set email alerts
|

Lightest Nuclei in UHECR versus Tau Neutrino Astronomy

Abstract: UHECR may be either nucleons or nuclei; in the latter case the Lightest Nuclei, as He, Li, Be, explains at best the absence of Virgo signals and the crowding of events around Cen-A bent by galactic magnetic fields. This model fit the observed nuclear mass composition discovered in AUGER. However UHECR nucleons above GZK produce EeV neutrinos while Heavy Nuclei, as Fe UHECR do not produce much. UHECR He nuclei at few tens EeV suffer nuclear fragmentation (producing low energetic neutrino at tens PeVs) but it su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 15 publications
2
27
0
Order By: Relevance
“…This opportunity is appealing to some authors because a hundred Mpc distance radius guarantees enough sources and homogeneity [6,18]; see Fig.3, 4. However, the unique UHECR particles that may travel so far, as we mentioned are protons, while PAO models and simulation composition recently favor a mix of lightest nuclei (He) together with light ones (Be, B, C and N), as we did suggested, independently, since long time [16,17], due to the problematic Virgo absence and the observed smearing angles.…”
Section: Far Uhecr Bending Path In Random Walkmentioning
confidence: 73%
See 1 more Smart Citation
“…This opportunity is appealing to some authors because a hundred Mpc distance radius guarantees enough sources and homogeneity [6,18]; see Fig.3, 4. However, the unique UHECR particles that may travel so far, as we mentioned are protons, while PAO models and simulation composition recently favor a mix of lightest nuclei (He) together with light ones (Be, B, C and N), as we did suggested, independently, since long time [16,17], due to the problematic Virgo absence and the observed smearing angles.…”
Section: Far Uhecr Bending Path In Random Walkmentioning
confidence: 73%
“…One of course may wonder if this is not the same case of the nearest AGN, as we did suggested since 2008 [16], made by light and lightest nuclei [17]. In this case, indeed, the bending angle is scaling with the atomic number Z (Z He = 2, Z Li = 3, Z Be = 4, Z B = 6).…”
Section: Lightest Nuclei Uhecr and Their Time Delaymentioning
confidence: 76%
“…We found that Cen A (the most active and nearby extragalactic AGN) is apparently the most shining UHECR source whose clustering (almost a quarter of the event) along a narrow solid angle (whose opening angular size is C171) [5] is convincing and in agreement with lightest nuclei [21,27,4]. However the main question is related to remaining majority of events.…”
Section: Overlapping G and Uhecr Mapsmentioning
confidence: 69%
“…The consequences of the UHECR composition and source distances should reflect, by interaction with relic photons, to UHE secondaries signals made by photo-pion production or photonuclear disruption as the well known GZK [2] or cosmo-genic neutrinos. The proton UHECR provide EeV neutrinos (muons and electron) whose flavor oscillation lead to tau neutrinos to be soon detectable [10,20] by upward tau air-showers; the UHECR lightest nuclei model provide only lower energy, tens PeV, neutrinos detectable in a very peculiar way by AUGER fluorescence telescopes or in ARGO array by horizontal t air-showers, or by Icecube km 3 neutrino telescopes [10,27,4] either by double bang [11], or by long muon at few PeV energy. Let us recall that ZeV UHE neutrinos in Z-Shower model are also possible source of horizontal Tau air-showers of maximal size and energy [10,9].…”
Section: A Two Decades Of Random Uhecr Puzzlesmentioning
confidence: 99%
“…However, the two earliest and main red colored UHECR Hot Spots were observed respectively by TA (2014-2016, North sky) and by Auger (2007-2018, South sky) are not correlated at all with the Virgo central direction. This remarkable Virgo absence is the Rosetta stone that forced us [19], a decade ago, toward the lightest [20] UHECR nuclei nature. Indeed we suggested the presence of a severe filter to stop the expected Virgo abundant UHECR events; if UHECR were protons the center of this map in the Fig.1 should shine brightly.…”
Section: The Virgo Absence and The Two Hot Spotsmentioning
confidence: 99%